Evaluation of fungicides against blight of cumin caused by Alternaria burnsii (Indian Journal of Arid Horticulture, 2025)
In India cumin is an important seed spice crop grown in the states of Rajasthan, Gujarat, Uttar Pradesh and Tamil Nadu. Rajasthan stands first in acreage (149 thousand ha) and production (27 thousand metric tonnes) (Anonymous, 2008). The crop suffers severely from blight disease which generally appears at the time of flowering or seed formation causing heavy losses in grain yield (Gemawat and Prasad, 1969; Bhatnagar et al., 1995). The present investigation are undertaken to evaluate the efficacy of different fungicides and one neem pesticide against severity of blight and yield of cumin. With a view to determine the efficacy of different fungicides and a neem pesticide on blight intensity and yield of cumin, an experiment in Randomized Block Design was laid out with three replications during rabi,2003-04 with RZ-19 variety.
Keywords: pesticide; fungicides; cumin; Anonymous; determine